(untitled) (RIAF. International Journal of Physical Activity, 2022)
During the last year, methodological strategies have been investigated to incorporate students with physical disabilities in Physical Education classes. It is essential that teachers are familiar with these strategies and apply them. The results indicate significant improvements in student participation and performance, contributing to creating an inclusive and motivating environment. The study was based on basic, theoretical and bibliographic research without experiments, with a descriptive design. 170 records were analyzed, excluding duplicates and articles according to their year of publication, and 15 relevant studies were selected. The databases used included Scielo, Dialnet and Scopus, using search terms related to inclusion in Physical Education. Various methodological strategies for the inclusion of students with physical disabilities in physical education have had a significant positive impact on participation and performance. Adaptations in curriculum and activities, together with approaches such as Universal Design for Learning, have facilitated greater integration and active participation, while reducing exclusion. Research has shown that detailed and personalized methodological strategies in Physical Education have a significant impact on the participation and performance of students with physical disabilities. The adaptation of activities and teaching methods reduces barriers and exclusion, optimizing integration and participation in classes.